Association of Birth-Weight, Obesity and Family History in the Development of Latent Autoimmune Diabetes in Adults (LADA) and Type 2 Diabetes Mellitus (Academia Journal of Medicine, 2020)
Background: A proportion of subjects with adult-onset autoimmune diabetes does not require insulin-therapy at the time of diagnosis and are  clinically similar to patients with type 2 Diabetes Mellitus (T2DM). Objectives: The present study was undertaken association of birth-weight,  obesity and family history in the development of latent autoimmune diabetes in adults (LADA) and type 2 Diabetes Mellitus. Subjects and  Methods: A total of 50 healthy controls, 50 type 2 diabetic and 50 patients with LADA were enrolled. Complete demographic details of all the  patients were obtained. Clinical examination of all the patients was carried out and medical history of all the patients was obtained. Detailed  medical history and family history of all the patients was recorded separately. A Performa was made and complete anthropometric parameters  were recorded. Body mass index (BMI) was calculated. All the results were recorded in Microsoft excel sheet and was analysed by SPSS  software. Results: While assessing association of birth-weight in the development of latent autoimmune diabetes in adults (LADA) and type 2  Diabetes Mellitus; it was observed that significantly higher proportion of patients of the diabetic group and the LADA group had low birth weight in comparison to the patients of the control group. While assessing association of family history of diabetes in the development of latent  autoimmune diabetes in adults (LADA) and type 2 Diabetes Mellitus; it was observed that significantly higher proportion of patients of the  diabetic group and the LADA group had positive family history of diabetes in comparison to the patients of the control group. While assessing  association of obesity in the development of latent autoimmune diabetes in adults (LADA) and type 2 Diabetes Mellitus; it was observed that  mean BMI of the patients of the diabetic group and the LADA group was significantly higher in comparison to the patients of the control  group. Conclusion: Low birth weight, obesity and positive family history of diabetes are important risk factors in the development of latent  autoimmune diabetes in adults (LADA) and type II diabetes.
Keywords: Birth weight; Diabetes; latent autoimmune diabetes in adults (LADA); Type 2 Diabetes Mellitus (T2DM)